2020
DOI: 10.1186/s12889-020-08642-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily almond consumption in cardiovascular disease prevention via LDL-C change in the U.S. population: a cost-effectiveness analysis

Abstract: Background: Heart disease is the leading cause of death in the United States. The U.S. Food and Drug Administration approved the health claim that 1.5 oz (42.5 g) of nut intake may reduce the risk of cardiovascular disease. Previous studies have focused on the cost-effectiveness of other foods or dietary factors on primary cardiovascular disease prevention, yet not in almond consumption. This study aimed to examine the costeffectiveness of almond consumption in cardiovascular disease primary prevention. Perspe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The US Food and Drug Administration approved a qualified health claim that eating 1.5 ounces (42.5 g)/day of tree nuts such as almonds as part of a diet low in saturated fat and cholesterol may reduce the risk of CHD [117]. A medical cost savings and quality of life analysis study in the US population using current US population CVD rates and the probabilities of elevated LDL-C increasing risk, disability, and death from CVD, found that increasing daily consumption of almonds up to 42.5 g/day could significantly reduce annual US CVD costs by about 25% and increase annual improvement in quality adjusted life years by 2% compared to <3 g almond/day average intake [118]. Other cost-benefit analyses show with high confidence that increased intake of foods such as almonds that lower glycemic index and glycemic load are causally correlated with reduced incidence of and medical costs related to T2 diabetes, which can reach 10% of the national health expenditures [119,120].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…The US Food and Drug Administration approved a qualified health claim that eating 1.5 ounces (42.5 g)/day of tree nuts such as almonds as part of a diet low in saturated fat and cholesterol may reduce the risk of CHD [117]. A medical cost savings and quality of life analysis study in the US population using current US population CVD rates and the probabilities of elevated LDL-C increasing risk, disability, and death from CVD, found that increasing daily consumption of almonds up to 42.5 g/day could significantly reduce annual US CVD costs by about 25% and increase annual improvement in quality adjusted life years by 2% compared to <3 g almond/day average intake [118]. Other cost-benefit analyses show with high confidence that increased intake of foods such as almonds that lower glycemic index and glycemic load are causally correlated with reduced incidence of and medical costs related to T2 diabetes, which can reach 10% of the national health expenditures [119,120].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…The high carbohydrate or saturated fatty acid diet is often associated with impaired glucose and lipid homeostasis which alters blood lipid profile in terms of elevated low density lipoprotein cholesterol (LDL-C), total cholesterol, apolipoprotein B (Apo B), and increases body weight which leads to cardiovascular risks. A recent study conducted by Wang et al [27] reported that 42.5 g almond consumption per day changes LDL-C which is also cost effective to prevent cardiovascular disease in the short term and potentially in the long term. Furthermore, studies conducted by Gulati et al [28] and Jalali-Khanabadi [29] reported that dietary almond can improve blood lipid profile by lowering total cholesterol (TC) and triglyceride, respectively in cardiovascular patients.…”
Section: Almond and Cardiovascular Diseasementioning
confidence: 99%
“…;Sharma et al, 2010;Turner-McGrievy et al, 2017;Schwarz et al, 2008). Large-scale clinical studies repeatedly demonstrate that foods affect the risk of incidence and mortality from common chronic diseases that are rapidly rising in society (L. Wang et al, 2018;De Koning et al, 2012;Kenfield et al, 2014;Tasevska et al, 2014;Salas-Salvadó et al, 2014;Esposito et al, 2017;Dicker et al, 2018;Muraki et al, 2013), thus bearing the potential to improve global population health in a cost-effective manner (Eussen et al, 2011;Yang et al, 2018;Wang et al, 2020). For example, FFIs can mitigate the effects of chronic, unresolved inflammation (Rein et al, 2019;K.…”
Section: Functional Food Ingredients and Healthmentioning
confidence: 99%